Емотивні прикметники у просторі художніх текстів - Melnychuk, Natalia (Видавничий дім «Гельветика», 2021)
The system approach to the study of English vocabulary needs to identify the laws of functioning of its individual components. In the modern studies of lexical semantics the use of a systematic approach in investigating of a certain phenomena provides a special value to the results of specific linguistic explorations. Actually, taking into account the systematic language allows you to study every semantic association of words as an integral part of the general system of language which allows a possibitity of modeling of semantic relations in the vocabulary. In turn, the contrasting study of the elements of language contributes to the detection of such properties of lexical semantics that reflect the peculiarities of lingual worldviews. The change in the paradigm of individual language units enables the investigation of some lexical and semantic phenomena in a new light, as well as the explanation of the features of their functioning in the language. Modern linguistic science is characterized by a vivacious interest in the study of the language as a socio-cultural phenomenon. Therefore the focus of many linguistic studies is a person and his role in organizing and using the language as a means of communication. In this case much attention is devoted to the emotional factor of an individual in the language, because everyday life of a human being can not be imagined without the expression of emotions with the means of a language. The study of the functioning of lexico-semantical field of adjectival emotive units as a fragment of the English language picture of the world interesting gives an interesting posibility to be observe its common and different features in comparison with the writer's individual picture of the world which plays an important role in an anthropocentrically directed linguistic research. This investigation gives an opportunity to observe the worldview of a nation – a bearer of the language and its immediate representative – a person. The analysis of the features of an artistic text (the semantic organization of which is quite complicated and heterogeneous by nature) allows you to identify the laws of the author’s artistic thinking which is revealed through the language of his texts, his selection and his artistic comprehension of the lexical means from the national linguistic fund.
EMOTIVE ADJECTIVES IN THE SCOPE OF ARTISTIC TEXTS
Keywords: емоція; емотивність; семантична структура; конотація; експресивність; оцінність; мовна картина світу; emotion; emotiveness; semantic structure; connotation; expressiveness; evaluation; linguistic picture of the world